DEVELOPMENT OF TWO DIMENSIONAL COUPLED WAVE, CURRENTS, SEDIMENT TRANSPORT AND MORPHOLOGY NUMERICAL MODEL IN NON COHESIVE MATERIAL BEACHES - NUGROHO (NIM 25507002), DWIYOGA
ABSTRACT: Study of nearshore hydrodynamics and sediment transport is presented in two dimensional numerical model. The two-way-coupled Advanced 2D Circulation And Transport Model (ADCIRC-2DTR) was applied as a one way coupled scheme to include wave refraction and diffraction model (Refdif) The ADCIRC-2DTR model based on Galerkin finite element method that solves three dimensional momentum equation and generalized wave continuity equation (GWCE) on a linear triangle shape function. The algorithm of non-cohesive sediment transport and morphology is included as two way coupled between hydrodynamics and transport calculation. Refdif model is based on finite difference techniques to solve the modified elliptic mild slope equations (EMSE). The radiation stresses calculated in Refdif are based on separation between momentum and pressure part in wave equation. Comparison results on analytical and numerical models in longshore current shows a good agreement in a graphical plot. The offshore breakwater simulation shows the deposition pattern of sediment and bathymetric change behind the structure as well.